2012
DOI: 10.1371/journal.pone.0047653
|View full text |Cite
|
Sign up to set email alerts
|

Dogs' Social Referencing towards Owners and Strangers

Abstract: Social referencing is a process whereby an individual uses the emotional information provided by an informant about a novel object/stimulus to guide his/her own future behaviour towards it. In this study adult dogs were tested in a social referencing paradigm involving a potentially scary object with either their owner or a stranger acting as the informant and delivering either a positive or negative emotional message. The aim was to evaluate the influence of the informant's identity on the dogs' referential l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 53 publications
(86 reference statements)
5
104
2
2
Order By: Relevance
“…This suggests a difference in their tendency to use their human caregivers for social referencing to guide their own understanding of such socially challenging, ambiguous situations. It is worth mentioning that looking at others when confronted with ambiguous events in order to use the emotional reactions of others to regulate their own behaviour is a 'behaviour tool' commonly used by human infants (Klinnert et al, 1986), and recently has been revealed in dogs (Merola et al, 2012). Our results raise the possibility that this functionally infant-analogue behaviour in dogs is one of the hallmarks of the fine-tunedness to humans of this domestic species.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This suggests a difference in their tendency to use their human caregivers for social referencing to guide their own understanding of such socially challenging, ambiguous situations. It is worth mentioning that looking at others when confronted with ambiguous events in order to use the emotional reactions of others to regulate their own behaviour is a 'behaviour tool' commonly used by human infants (Klinnert et al, 1986), and recently has been revealed in dogs (Merola et al, 2012). Our results raise the possibility that this functionally infant-analogue behaviour in dogs is one of the hallmarks of the fine-tunedness to humans of this domestic species.…”
Section: Discussionmentioning
confidence: 56%
“…In this controlled game situation the endeavour to involve the passive owner in the interaction by gazing or approaching might have been an alternative solution to cope with the ambiguity (see also Merola et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Unreachable food task was followed by the Potentially dangerous object task (for a similar task see Merola et al, 2012). This task was used to explore the dogs' tendency to display referential looking (a form of information seeking behavior when facing a potentially dangerous object) towards humans, and, whether intranasal administration of oxytocin could modify this behavior in the two distinct dog breeds (for video protocol and photograph see Supplementary material S2).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…These have led to a wide range of behavioral analogies between humans and dogs (Topál et al, 2009) and dogs often show human infant-like communicative receptivity in interaction with humans (Miklósi and Topál 2012). For example, dogs often use eye gaze cues in a flexible manner; they show a tendency to make eye contact with their owner in unsolvable tasks (Gaunet, 2008;Miklósi et al, 2005) and alternate their gaze between the potential human helper and the object of desire (Gaunet and Deputte 2011;Merola et al, 2012;Miklósi et al, 2000). Gaze alternation is a three-step sequence whereby the signaler alternates its gaze directly between a target and the partner, and it seems to fulfill the requirements of active information sharing since looking at the human partner − which is subsequently followed by looking towards the target − is functionally referential signaling (Lakatos et al, 2009;Soproni et al, 2001).…”
Section: Introductionmentioning
confidence: 99%